Preparation and characterization of hydrophobic alumina planar membranes for water desalination. Issue 2 (February 2015) - Ren, Chunlei; Fang, Hong; Gu, Jianqiang; Winnubst, Louis; Chen, Chusheng
Abstract A planar alumina membrane was prepared by a one-step phase-inversion tape casting method. The membrane consisted of a thick support layer with finger-like large pores and a thin separation layer containing small pores with an average diameter of ∼0.76 μm. The overall porosity of the membrane was ∼59%, as determined with the Archimedes method, and the porosity associated with the large, finger-like pores in the support layer was ∼34% as derived from image analysis. The surface of this alumina membrane was converted from hydrophilic to hydrophobic via grafting with a fluoroalkylsilane. The water desalination performance was tested by exposing the hydrophobic separation layer to an aqueous solution of 2 wt.% NaCl at 80 °C, while a sweep of distilled water at 20 °C was used, resulting in a water flux of 19.1 L m−2 h−1 and a salt rejection over 99.5%. Due to the excellent water desalination performance, the hydrophobic porous ceramic membrane holds promise for practical applications.